Advances in phytoplankton population ecology in the Pearl river estuary - Chen, Wenlong; Guo, Fang; Huang, Weijie; Wang, Jianguo; Zhang, Min; Wu, Qian (Frontiers in Environmental Science, 2023)
Phytoplankton is an important primary producer of the estuarine ecosystem, which is essential for the biogeochemical cycle of water elements and nutrient transfer. The Pearl River estuary (PRE) is a dynamically complex estuary, and the environment of PRE is significantly impacted by anthropogenic activities, variation of phytoplankton community structure in the PRE are complex. This review aims to compare phytoplankton species, species diversity, and abundance variation characteristics from the 1980s and 2020s, evaluate the overall trend of phytoplankton in the PRE, and discuss the main environmental factors affecting phytoplankton growth in the PRE. The data from the past 40 years in PRE showed that the number of phytoplankton species significantly decreased (p < 0.05). There was no significant difference in the abundance of phytoplankton at the 10-year scale, however, the fluctuation range of the abundance has increased. Under the conditions of a decreasing species number and no significant difference in abundance, the species diversity of phytoplankton showed a downward trend. In addition, the dominant phytoplankton species in the nearshore waters were relatively homogenous, and the abundance of phytoplankton in the nearshore waters was higher than that in the open waters, which suggested that human activities have a great influence. This review can form the basis for facilitating health management in the PRE ecosystem. Further, relevant guidelines can be developed and implemented for promoting the ecological health of the Guangdong-Hong Kong-Macao Greater Bay Area and ensuring its sustainable development.